2021
DOI: 10.1002/cbdv.202100389
|View full text |Cite
|
Sign up to set email alerts
|

GDP Induces PANC‐1 Human Pancreatic Cancer Cell Death Preferentially under Nutrient Starvation by Inhibiting PI3K/Akt/mTOR/Autophagy Signaling Pathway

Abstract: Pancreatic tumors are hypovascular, which leads to a poor nutrient supply to support the aggressively proliferating tumor cells. However, human pancreatic cancer cells have extreme resistance to nutrition starvation, which enables them to survive under severe metabolic stress conditions within the tumor microenvironment, a phenomenon known as “austerity” in cancer biology. Discovering agents which can preferentially inhibit the cancer cells’ ability to tolerate starvation conditions represents a new generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Here, we observed that acid-selected Panc-1 cells, in line with their extreme resistance to stress metabolic conditions [47] and chemotherapeutics, had a decreased basal cell death compared to the non-selected cells at both pH e 6.7 and 7.4, while acid selection in MiaPaCa2 cells increased basal death compared to the control cells at both pH e s (Figure 2). These results are also in accordance with other studies, which demonstrated that Panc-1 cells exhibit higher stemness features than MiaPaCa-2 cells [48].…”
Section: Discussionmentioning
confidence: 66%
“…Here, we observed that acid-selected Panc-1 cells, in line with their extreme resistance to stress metabolic conditions [47] and chemotherapeutics, had a decreased basal cell death compared to the non-selected cells at both pH e 6.7 and 7.4, while acid selection in MiaPaCa2 cells increased basal death compared to the control cells at both pH e s (Figure 2). These results are also in accordance with other studies, which demonstrated that Panc-1 cells exhibit higher stemness features than MiaPaCa-2 cells [48].…”
Section: Discussionmentioning
confidence: 66%
“…In earlier studies, PANC-1 cancer cells have been shown to survive for more than 3 days, even in the complete absence of essential nutrients such as glucose, amino acids, and serum. This survival capacity of cancer cells under conditions of nutrient starvation is commonly called ‘austerity’ [ 25 , 50 ]. The search for a candidate that eliminates the cancer cells’ tolerance to nutrition starvation is a unique approach to anticancer drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is regulated in a variety of ways, especially PI3K/AKT/mTOR pathway. The PI3K/AKT/mTOR/autophagy pathways play a crucial role in regulating tumor progression and maintaining the balance of the tumor microenvironment ( Sun et al, 2021 ; Wu et al, 2020 ; Yoshida, 2017 ; Zhang et al, 2011 ). Nevertheless, the research into the regulatory interplay between HSP90B1 and autophagy remains sparse, with the specific mechanisms of HSP90B1 action in HNSC yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%